Violence against Women and Girls: Lessons from South Asia - Solotaroff, JenniferL. (World Bank, 2015)
Violence against Women and Girls: Lessons from South Asia examines the prevalence and factors associated with various types of violence against women and girls in Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. It analyzes the nature of violence throughout the life cycle and highlights gaps where intensive research or interventions might be undertaken. Analyses of the most recent data reveal that South Asia has the world?s highest levels of excess female child mortality and child marriage. The prevalence of intimate partner violence also remains unacceptably high, particularly for married adolescents. Reliable data are limited for other forms of violence.